2011
DOI: 10.1016/s1734-1140(11)70627-2
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor activity changes in female adolescent and adult rats during repeated treatment with a cannabinoid or club drug

Abstract: Adolescents and young adults of both sexes are the primary consumers of "club" drugs; yet, most of the mechanistic preclinical research in this area has been performed in adult male rodents. The purpose of this study was to evaluate the acute and repeated effects of drugs that are commonly abused by adolescents in female adolescent and adult rats in a rodent model of behavioral sensitization. During two five-day periods separated by a two-day break, rats were injected daily with saline or with one of the follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…In male rats, ketamine-induced locomotor sensitization has been observed in doses as low as 5 mg/kg and as high as 50 mg/kg (Popik et al , 2008; Botanas et al , 2015). Additionally, one study reported locomotor sensitization at a dose of 10 mg/kg in female rats (Wiley et al , 2011). The present study demonstrates that repeated, intermittent ketamine administration at a dose of 5 mg/kg, but not 2.5 mg/kg, produces behavioral sensitization in male rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In male rats, ketamine-induced locomotor sensitization has been observed in doses as low as 5 mg/kg and as high as 50 mg/kg (Popik et al , 2008; Botanas et al , 2015). Additionally, one study reported locomotor sensitization at a dose of 10 mg/kg in female rats (Wiley et al , 2011). The present study demonstrates that repeated, intermittent ketamine administration at a dose of 5 mg/kg, but not 2.5 mg/kg, produces behavioral sensitization in male rats.…”
Section: Discussionmentioning
confidence: 99%
“…Upstream signaling molecules such as brain-derived neurotrophic factor (BDNF) can influence downstream signaling targets such as ΔfosB, a transcription factor heavily associated with addiction (Wiley et al , 2011; Li and Wolf, 2015). Thus, the present study sought to examine whether protein expression of the aforementioned targets could be affected by low-dose ketamine as they are affected by other drugs of abuse like cocaine.…”
Section: Discussionmentioning
confidence: 99%
“…The few exceptions were all from the same lab (Wiley, 2003; Wiley et al, 2011, 2007). In the first study (Wiley, 2003), female mice were more sensitive than males to acute THC-induced hyperlocomotion; after 2.5 days of twice-daily THC injections, only females showed dose-dependent changes in THC’s effect.…”
Section: Introductionmentioning
confidence: 99%
“…This research was supported by US National Institute on Drug Abuse Grant DA19239, DA09236, and DA02775. The authors acknowledge and appreciate the exceptional assistance of Divya Lakhaney, Elyssa Berg, Michael Harakas, Sarah Badach, Bennett Wechsler, and Ursula Rogers in data collection.…”
mentioning
confidence: 99%